2021
DOI: 10.1371/journal.pone.0246690
|View full text |Cite
|
Sign up to set email alerts
|

Shedding and transmission of a live attenuated influenza A virus vaccine in pre-weaned pigs under field conditions

Abstract: Influenza A virus (IAV) is one of the most important respiratory viruses affecting pig health and vaccination is the most common strategy to control influenza infections. In this field study we assessed the onset and duration of shedding of a live attenuated influenza virus (LAIV) vaccine, its ability to transmit to non-vaccinated pigs and whether the LAIV could be aerosolized and detected in the environment. Thirty-three litters (n = 33) of a farm using the LAIV vaccine were selected for the study, a subset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The marketed LAIV contained two subtypes of IAV-S; H1N1 strain A/swine/Minnesota/37866/1999 and the H3N2 strain A/swine/Texas/4199-2/1998 and was licensed for piglets as young as 2 days of age. While experimental transmission studies showed limited LAIV shedding after vaccination, minimal transmission to non-vaccinated pigs, and no evidence of reassortment between endemic IAV-S ( Lopez Moreno et al., 2021 ), later surveillance of U.S. swine populations revealed evidence of reassortment between the LAIV vaccine virus and circulating endemic H1 and H3 field strains ( Sharma et al., 2020 ), indicating that experimental conditions cannot always recapitulate field conditions. This licensed LAIV was subsequently removed from commercial use in 2020 and highlights the need for continued IAV-S surveillance to identify asymptomatically infected pigs and limit the risk of reassortment during vaccination.…”
Section: Licensed Vaccines Against Iav-smentioning
confidence: 99%
“…The marketed LAIV contained two subtypes of IAV-S; H1N1 strain A/swine/Minnesota/37866/1999 and the H3N2 strain A/swine/Texas/4199-2/1998 and was licensed for piglets as young as 2 days of age. While experimental transmission studies showed limited LAIV shedding after vaccination, minimal transmission to non-vaccinated pigs, and no evidence of reassortment between endemic IAV-S ( Lopez Moreno et al., 2021 ), later surveillance of U.S. swine populations revealed evidence of reassortment between the LAIV vaccine virus and circulating endemic H1 and H3 field strains ( Sharma et al., 2020 ), indicating that experimental conditions cannot always recapitulate field conditions. This licensed LAIV was subsequently removed from commercial use in 2020 and highlights the need for continued IAV-S surveillance to identify asymptomatically infected pigs and limit the risk of reassortment during vaccination.…”
Section: Licensed Vaccines Against Iav-smentioning
confidence: 99%